Recovery of uncultivated and abandoned land. The “new season” of Italian legislation towards environmental objectives and the promotion of access to land by young people - Strambi , Giuliana (Przegląd Prawa Rolnego, 2018)
In Italy the recovery of uncultivated and abandoned land was alive for several years after the first world war, but not always with satisfactory results. The present paper aims to highlight the reasons for the recent renaissance of the Regions’ interest in this issue, which have lately regulated again the allocation of uncultivated and abandoned land under the new framework of a discipline termed “land banks.” Following the example of the regional legislations, which have environmental goals, the State has recently created “land banks” that aim to provide opportunities for young people to gain access to land, especially in Southern Italy, eventually curbing the problem of the ageing of the farmers. The paper will examine the various disciplines, framing them in the context of EU policies for the rational use of natural resources and for the development of marginal rural areas, in order to highlight the key issues involved.